Sensory Quality Characteristics of Fermented Arabica Coffee (Coffea arabica L.) Fruit Liquid as a Potential Functional Beverage - Syahirman Hakim; Masrura Hayati; Irwansyah; Akmal Izwar; Baihaqi (Fakultas Pertanian Universitas Almuslim Bireuen Aceh, 2025)
Arabica coffee fermentation liquid is a by-product of coffee processing with considerable potential to be developed as a functional beverage because it contains bioactive compounds produced through microbial metabolism during fermentation. However, information regarding the optimum fermentation duration to achieve the best sensory quality remains limited. This study aimed to evaluate the effect of fermentation duration on the sensory characteristics of Arabica coffee fermentation liquid. A Completely Randomized Design (CRD) with three fermentation periods (5, 10, and 15 days), each conducted in triplicate, was employed. Sensory quality was evaluated using a hedonic test covering color, aroma, taste, acidity, body, aftertaste, clarity, and overall acceptability. Data were analyzed using one-way analysis of variance (ANOVA), followed by Duncan's Multiple Range Test (DMRT) at a 5% significance level. Fermentation duration significantly affected (p<0.05) all sensory attributes. The 10-day fermentation produced the highest scores for color (7.63), aroma (7.81), taste (7.74), acidity (7.42), body (7.39), aftertaste (7.54), clarity (7.48), and overall acceptability (7.68). It can be concluded that a 10-day fermentation period is the optimum condition for producing Arabica coffee fermentation liquid with superior sensory quality. These findings provide scientific evidence supporting the utilization of coffee fermentation liquid as a value-added functional beverage and offer practical insights for product diversification and sustainable development of the Arabica coffee industry.